Diagnosing a Halal Certification System for Cosmetics: The Viable System Model Approach - Khairul Akmaliah Adham; Adlin Masood; Alina Abdul Rahim; Nur Sa’adah Muhamad (Springer Link, 2024)
Indexed by WOS/Scopus/ERA